Метод усреднения дискретных систем и его приложение к задачам управления - Плотников, В.А.; Плотникова, Л.И.; Яровой, А.Т. (Нелінійні коливання, 2004)
Запропоновано i обґрунтовано деякi алгоритми часткового i повного усереднення систем дискретних рiвнянь i включень. На основi отриманих схем усереднення побудовано алгоритми чисельно-асимптотичного розв’язання задач оптимального управлiння дискретними системами. We propose and substantiate certain algorithms for partial and complete averaging for systems of discrete equations and inclusions. Using the obtained averaging schemes we construct algorithms for finding solutions, in a numerical-analytical way, of optimal control problems for discrete systems.